The third giant of english literature, John Milton and the english EPIC Paradise Lost - Chérrez, Andrea
This work is destined to show and analyze the life and works of the Third Giant of English Literature, John Milton. The first chapter will focus on Milton?s life and education. Miltons works mirror his life, since he wrote poems and sonnets on his own personal experiences and losses. His education is the best he could receive, first by private tutors at home, followed by entrance into St. Paul?s School, and later Christ College, Cambridge. In the second chapter, some of Miltons most important works will be analyzed. He not only wrote poetry but also important prose works addressing many kinds of themes, which greatly influenced his time, and they continue doing so. The third chapter is destined to analyze, Milton?s best masterpiece, Paradise Lost, a work which is agreed to be the greatest epic, perhaps even the greatest work of literature written in the English language. Milton wrote this epic in spite of being totally blind. This poem tells us the biblical story of the fall of Adam and Eve, and the story of Satan?s rebellion against God. Milton took these stories from the Bible; however, he expanded them into a very long, detailed, and narrative poem full of imagery and details. Finally, in the last chapter, some differences and similarities between Milton?s and the Bible?s version of the fall of man will be analyzed. Paradise Lost differs in some aspects and details from the Bible account; however, these small differences do not affect the Bible?s main purpose and teaching.